2021
DOI: 10.1038/s41436-020-00967-0
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of monogenic etiologies of nonimmune hydrops fetalis

Abstract: Hydrops Fetalis (HF), accumulation of fluid in two or more fetal compartments, is life-threatening to the fetus. Genetic etiologies include many chromosomal and monogenic disorders. Despite this, the clinical workup typically evaluates limited genetic targets. To support broader molecular testing of pregnancies with HF, we cataloged the spectrum of monogenic disorders associated with nonimmune hydrops fetalis (NIHF). We performed a systematic literature review under PROSPERO tag CRD42018099495 of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 26 publications
0
54
0
Order By: Relevance
“…Even though, it is still a challenging task to elucidate the exact etiology of NIHF, which is essential for prenatal counseling and determination of the appropriate therapy if available (Norton et al, 2015). In recent years, whole exome sequencing (WES) has been gradually applied to identify de-novo mutations for evaluation of fetal abnormalities, which is insufficient by conventional molecular approaches such as karyotyping and chromosomal microarray analysis (CMA), including NIHF (Sparks et al, 2020;Quinn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though, it is still a challenging task to elucidate the exact etiology of NIHF, which is essential for prenatal counseling and determination of the appropriate therapy if available (Norton et al, 2015). In recent years, whole exome sequencing (WES) has been gradually applied to identify de-novo mutations for evaluation of fetal abnormalities, which is insufficient by conventional molecular approaches such as karyotyping and chromosomal microarray analysis (CMA), including NIHF (Sparks et al, 2020;Quinn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fotiou et al identified 10 PIEZO1 mutations in six families which cosegregate with the GLD phenotype. The affected individuals suffer from in utero demise, complete resolution after birth, the reappearance of lymphoedema in peripheries at early childhood, or recurrent facial cellulitis (Quinn et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, the definitive diagnostic yield of CMA over standard G-banding karyotyping is moderate and, following exclusion of the aforementioned causes, up to 50% of cases of NIHF remain unexplained, with a significant proportion thought to be secondary to single-gene variants 5 . Over 170 genes have been identified as being associated with NIHF and, until the recent emergence of next-generation sequencing (NGS), testing for such conditions has relied on targeted gene testing and enzyme assays 3,6 . Single-gene causes of NIHF are associated with significant risks of perinatal death or neurodevelopmental sequelae 2 .…”
Section: Introductionmentioning
confidence: 99%